ANALISIS PENGGUNAAN MEDIA RAINBOW CIKAS DALAM PEMAHAMAN KONSEP PECAHAN SISWA KELAS IV - Elis Subartini; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Mathematics is one of the important subjects that underlie other sciences. Rapid progress in the field of information and communication technology today is also based on the development of mathematics . One of the ways that the author tries to concretize fractional material is to use real objects. The display that the author uses is rainbow cikas media, which is media made from used CDs, which are widely available and are considered useless waste.The purpose of this study was to improve the understanding of the concept of fractions with the Rainbow Cikas media in the fourth grade students. The focus of the research is on increasing the understanding of the concept of fractions which is marked by an increase in the average value of daily tests, an increase in the percentage of students who reach the KKM, and student responses to learning fractions using Rainbow Cikas media.The data sources are students and teachers. Data collection through observation, interview, documentation and data triangulation techniques. Triangulation is defined as a data collection technique that combines various data collection techniques and existing data sources. The validity of the data consists of 4 tests, namely the transferability test credibility test, reliability test, confirmability test, so the researcher collects data while testing the credibility of the data, namely checking the credibility of the data with various data collection techniques and various sources. The criteria for research success are measured by a minimum grade point average of 70, a minimum of 80% of students have reached the specified KKM of 70, and a minimum of 80% of students respond to learning in a good category.The results showed that the use of Rainbow Cikas media could improve the understanding of the concept of fractions. This was evident from the achievement of all the success criteria set out in the study. Among them the test results showed an increase in the average grade of the class, the percentage of students who achieved the KKM score set by the school increased, and student responses to learning the concept of fractions with Rainbow Cikas media were in the good category.